Ramucirumab with cisplatin and fluoropyrimidine as first-line therapy in patients with metastatic gastric or junctional adenocarcinoma (RAINFALL): a double-blind, randomised, placebo-controlled, phase 3 trial. Issue 3 (March 2019) - ,; Luft, Alexander V.; Karaseva, Nina A.; Kowalyszyn, Rubén Dario; Hernandez, Carlos Alberto; Csoszi, Tibor; De Vita, Ferdinando; Pfeiffer, Per; Sugimoto, Naotoshi; Kocsis, Judit; Csilla, Andràs; Bodoky, Gyorgy; et al.
Summary: Background: VEGF and VEGF receptor 2 (VEGFR-2)-mediated signalling and angiogenesis can contribute to the pathogenesis and progression of gastric cancer. We aimed to assess whether the addition of ramucirumab, a VEGFR-2 antagonist monoclonal antibody, to first-line chemotherapy improves outcomes in patients with metastatic gastric or gastro-oesophageal junction adenocarcinoma. Methods: For this double-blind, randomised, placebo-controlled, phase 3 trial done at 126 centres in 20 countries, we recruited patients aged 18 years or older with metastatic, HER2-negative gastric or gastro-oesophageal junction adenocarcinoma, an Eastern Cooperative Oncology Group (ECOG) performance status of 0 or 1, and adequate organ function. Eligible patients were randomly assigned (1:1) with an interactive web response system to receive cisplatin (80 mg/m 2, on the first day) plus capecitabine (1000 mg/m 2, twice daily for 14 days), every 21 days, and either ramucirumab (8 mg/kg) or placebo on days 1 and 8, every 21 days. 5-Fluorouracil (800 mg/m 2 intravenous infusion on days 1–5) was permitted in patients unable to take capecitabine. The primary endpoint was investigator-assessed progression-free survival, analysed by intention to treat in the first 508 patients. We did a sensitivity analysis of the primary endpoint, including a central review of CT scans. Overall survival was a key secondary endpoint. This study is registered with ClinicalTrials.gov, number NCT02314117 . Findings: Between Jan 28, 2015, and Sept 16, 2016, 645 patients were randomly assigned to receive ramucirumab plus fluoropyrimidine and cisplatin (n=326) or placebo plus fluoropyrimidine and cisplatin (n=319). Investigator-assessed progression-free survival was significantly longer in the ramucirumab group than the placebo group (hazard ratio [HR] 0·753, 95% CI 0·607–0·935, p=0·0106; median progression-free survival 5·7 months [5·5–6·5] vs 5·4 months [4·5–5·7]). A sensitivity analysis based on central independent review of the radiological images did not corroborate the investigator-assessed difference in progression-free survival (HR 0·961, 95% CI 0·768–1·203, p=0·74). There was no difference in overall survival between groups (0·962, 0·801–1·156, p=0·6757; median overall survival 11·2 months [9·9–11·9] in the ramucirumab group vs 10·7 months [9·5–11·9] in the placebo group). The most common grade 3–4 adverse events were neutropenia (85 [26%] of 323 patients in the ramucirumab group vs 85 [27%] of 315 in the placebo group), anaemia (39 [12%] vs 44 [14%]), and hypertension (32 [10%] vs 5 [2%]). The incidence of any-grade serious adverse events was 160 (50%) of 323 patients in the ramucirumab group and 149 (47%) of 315 patients in the placebo group. The most common serious adverse events were vomiting (14 [4%] in the ramucirumab group vs 21 [7%] in the placebo group) and diarrhoea (11 [3%] vs 19 [6%]). There were seven deaths in each group, either during study treatment or within 30 days of discontinuing study treatment, which were the result of treatment-related adverse events. In the ramucirumab group, these adverse events were acute kidney injury, cardiac arrest, gastric haemorrhage, peritonitis, pneumothorax, septic shock, and sudden death (n=1 of each). In the placebo group, these adverse events were cerebrovascular accident (n=1), multiple organ dysfunction syndrome (n=2), pulmonary embolism (n=2), sepsis (n=1), and small intestine perforation (n=1). Interpretation: Although the primary analysis for progression-free survival was statistically significant, this outcome was not confirmed in a sensitivity analysis of progression-free survival by central independent review, and did not improve overall survival. Therefore, the addition of ramucirumab to cisplatin plus fluoropyrimidine chemotherapy is not recommended as first-line treatment for this patient population. Funding: Eli Lilly and Company.